The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d3nh00008g
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of plasmonic hot spots with shurikens for superchiral SERS-based enantiomer recognition

Abstract: Detection of enantiomers is a challenging problem in drug development as well as environmental and food quality monitoring where traditional optical detection methods suffer from low signals and sensitivity. Application...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…For the point C located exactly on the symmetry axis, the total decay rate and radiative decay rate of the RCP and LCP emitters are almost equal (Figure h). Note also that plasmonic nanostructures and metasurfaces with intrinsic structural chirality have been reported to achieve chiral-dependent emission behaviors such as chiral photoluminescence and surface-enhanced Raman scattering–chiral anisotropy, as well as an enantiomer-dependent tailored immunological response. ,, Here, it is shown that chiral-dependent QE exists even in the symmetric antenna, which lacks the chiral near-field and structural chirality. In addition to previous studies on chiral sensing, chiral QE can provide an additional perspective for detecting enantiomers to optimize the sensitivity of chiral identification.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…For the point C located exactly on the symmetry axis, the total decay rate and radiative decay rate of the RCP and LCP emitters are almost equal (Figure h). Note also that plasmonic nanostructures and metasurfaces with intrinsic structural chirality have been reported to achieve chiral-dependent emission behaviors such as chiral photoluminescence and surface-enhanced Raman scattering–chiral anisotropy, as well as an enantiomer-dependent tailored immunological response. ,, Here, it is shown that chiral-dependent QE exists even in the symmetric antenna, which lacks the chiral near-field and structural chirality. In addition to previous studies on chiral sensing, chiral QE can provide an additional perspective for detecting enantiomers to optimize the sensitivity of chiral identification.…”
Section: Resultsmentioning
confidence: 81%
“…The superscript ± indicates the right/left circularly polarized (RCP/LCP) emitter. Assuming that the collection efficiency remains constant when the chiral emitter is coupled to the nanostructure, the chiral detection sensitivity can be enhanced by nanostructures that generate near-field with increased local field intensity or chiral asymmetry. For instance, recent studies have achieved chiral-sensitive enantiomeric discrimination in surface-enhanced Raman scattering response or luminescence from fluorescent species. However, most previous works focused on the excitation enhancement during chiral sensing by engineering nanostructures to feature enhanced near-field optical chirality (OC). To further understand the impact of the chiral near-field upon the emission process of molecules, we focus on the chiral response of luminescence QE in plasmonic nanostructures. Furthermore, the QE in TMDCs plasmonic hybrid differs for valley excitons with different spins. , Thus, chiral-dependent QE may improve the sensitivity of enantiomers’ chiral recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, measurement of L-Cys, TP, and its derivatives levels is important for clinical diagnosis and environmental restoration. Many optical as well as nonoptical analytical techniques have been used so far to detect thiols, such as chemiluminescence, voltammetry, fluorescence, photoelectrochemical methods, time-resolved photoluminescence spectroscopy, high-performance liquid chromatography (HPLC), electrochemical methods, and a handful of surface-enhanced Raman spectroscopy (SERS)-based methods. However, most of these techniques suffer from individual drawbacks such as interference from other analytes, time-consuming operation, complex substrate preparation, and difficult synthesis of fluorescent probes. Additionally, the choice of analytical method to quantify the small molecule L-Cys and TPs should be based on the lowest limit of quantification (LOQ) because the lowest LOQ would allow for detection and quantification in the smallest amount of analytical sample, minimizing the volume of the sample collection.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the similar SERS signals obtained on D-Au-HO and D-Au-HDO, D-Au-HO exhibits a higher chiral discrimination ability than D-Au-HDO, indicating the enantioselective interaction of chiral electromagnetic fields and chiral molecules. This effect is also confirmed by excitation wavelength-dependent experiments and widely supported by previous literature. ,, We conducted experiments on different excitation wavelengths. Illuminating the D-Au-HO with 540 nm light achieves a higher value of chiral discriminating ability than illuminating with 620 nm light, owing to the high chiroptical response around 540 nm (Figure S21a,c), despite the similar plasmon-enhanced currents in both cases (Figures S14 and S21b).…”
mentioning
confidence: 99%
“…This effect is also confirmed by excitation wavelength-dependent experiments and widely supported by previous literature. 31,34,52 We conducted experiments on different excitation wavelengths. Illuminating the D-Au-HO with 540 nm light achieves a higher value of chiral discriminating ability than illuminating with 620 nm light, owing to the high chiroptical response around 540 nm (Figure S21a,c), despite the similar plasmon-enhanced currents in both cases (Figures S14 and S21b).…”
mentioning
confidence: 99%